International curriculum for undergraduate sonographer education in China during the COVID-19 era: International remote teaching mode vs. domestic on-site teaching mode - Qiu, Tingting; Lu, Qiang; Luo, Yan; Ling, Wenwu (Frontiers in Public Health, 2022)
Background Sichuan University West China Medical School was the first institution in China to develop an undergraduate sonographer education program in 2016. This program was certificated by American Registry for Diagnostic Medical Sonography (ARDMS) and students are qualified for the ARDMS credential verification test. In this 4-year program, the international curriculum of ultrasound physics and hemodynamics was set for students in the third year since 2018. This study is aimed to compare the teaching effect of international remote teaching mode and domestic on-site teaching mode of this international curriculum before and during the COVID-19 pandemic. Methods All undergraduate sonographer students after completing ultrasound physics and hemodynamics in the academic years 2018–2019 (30 students; before the COVID-19 pandemic) and 2020–2021 (47 students; during the COVID-19 pandemic) were included in the study. The scores of 77 students were analyzed for their curriculum. Independent samples t-test or Mann–Whitney test was employed to compare students' scores before and during the COVID-19 pandemic. The Chi-square test was used to compare students' feedback about this curriculum through an online self-administered questionnaire. A p < 0.05 was considered statistically significant. Results Total scores were comprised of four parts: in-class tests, homework, mid-term, and final exam scores. The mean in-class test score for domestic on-site teaching mode during the COVID-19 pandemic was significantly higher than that for international remote teaching mode before the COVID-19 pandemic. However, there was no observed a statistically significant difference in homework, mid-term, final exam, and total scores between the two types of teaching modes. For questionnaire feedback, no significant difference was observed between the two groups regarding the satisfaction toward teachers, class atmosphere, teaching mode, curriculum content, exam difficulty, scores, and knowledge students gained. For the overall evaluation of the curriculum, 73.3% (22/30) of students were very satisfied before the COVID-19 pandemic, while 44.7% (21/47) of students felt very satisfied during the COVID-19 pandemic (p = 0.02). Conclusion The general teaching effect of domestic on-site teaching mode during the COVID-19 pandemic was comparable to that of international remote teaching mode before the COVID-19 pandemic, and domestic on-site teaching mode may provide a better in-class teaching effect.